Thermo‐time domain reflectometry to evaluate unsaturated soils contaminated with nonaqueous phase liquids - Ju, Z. (2020)
An independent experiment was conducted to compare the NAPL content estimated using the new calibration equation and the known content. The results show that the NAPL content had no effect on the dielectric constant, and the soil dielectric constant maintained a steady value at the same water content, which ranged from 5 to 20 with increasing water content. At a constant water content, the soil electrical conductivity slightly decreased as the NAPL content increased. The soil thermal conductivity generally increased with the addition of NAPLs. There was a linear correlation between the total liquid content in the soil and the volumetric heat capacity. A new calibration equation was established to determine the NAPL saturation in soils from the relationship between the soil saturation, volumetric heat capacity, and water content as measured by time domain reflectometry. Independent validation indicated that the calibration equation was able to provide accurate NAPL saturation data in the laboratory, with a RMSE of 0.042.